The Effect Of The Variable Of Tax Expense, Tunneling Incentive And Leverage On Transfer Pricing With Profitability As A Moderating Variable - Sulhendri Sulhendri; Sabaruddin Sabaruddin; Septi Wulandari Chairina (Economy Deposit Journal (E-DJ), 2023)
This study aims to examine the effect of the variable of tax expense, tunneling incentive and leverage on transfer pricing with profitability as a moderating variable. This study is quantitative using secondary data obtained from manufacturing companies with food and beverage sector listed on the Indonesia Stocks Exchange (IDX) in 2015-2020. The sampling process used a purposive sampling technique using several criteria that have been determined by the researcher. The data analysis technique used is panel data analysis using the statistical application of E-Views 12 as a data tool. The results of this study indicate that tax expense, tunneling incentive and leverage on transfer pricing together affect transfer pricing. Partially, tax expense and leverage have a positive insignificants effect on transfer pricing. Tunneling incentive has a positive significants effect on transfer pricing. And then, profitability has a positive significant with tax expense on transfer pricing